Characterization, thermostable mechanism, and molecular docking of a novel glucose-tolerant β-glucosidase/β-galactosidase from the GH1 family isolated from Rehai hot spring - Huang, Yu-Ying; Zhu, Dan; Yang, Li-Quan; Ortúzar, Maite; Yang, Zheng-Feng; Lv, Zhi-Hua; Xie, Kai-Qing; Jiang, Hong-Chen; Li, Wen-Jun; Yin, Yi-Rui (Frontiers in Microbiology, 2025)
IntroductionAs a renewable alternative to fossil fuels, second-generation bioethanol production relies heavily on efficient lignocellulose conversion, with β-glucosidase playing a critical role.MethodsThis study focused on the β-glucosidase gene y50bg4 discovered in the Tengchong Rehai metagenome. The recombinant enzyme Y50Bg4 was obtained through PCR amplification, cloning, and expression. It was subsequently separated and purified using a Ni-NTA affinity chromatography column, and its enzymatic properties were analyzed.ResultsEnzymatic characterization revealed that Y50Bg4 efficiently hydrolyzes substrates like cellobiose, pNPGlc, and lactose. Y50Bg4 achieved optimal activity at 60°C and pH 6.0, maintaining 100% stability after 2 h of incubation at 60°C. The residual activity remained above 60% after 24 h of incubation across a pH range of 4.0 to 10.0. Kinetic constants analysis showed Km values of 4.69 mg/mL for cellobiose and 0.53 mM for pNPGlc, with Vmax values of 39.71 μmol/min/mg and 20.39 μmol/min/mg, respectively. Furthermore, the enzyme exhibits exceptional glucose tolerance, with Y50Bg4 retaining over 80% of its activity even at a glucose concentration of 3,000 mM. In practical applications, Y50Bg4 can work synergistically to degrade corn straw when combined with commercial cellulase. When Y50Bg4 (0.05 mg/mL) was added to the commercial cellulase reaction system, the glucose yield from corn straw increased by 11.6% after a reaction period of 24 h at 50°C. The results indicate that Y50Bg4 exhibits the activities of both β-glucosidase and β-galactosidase. Molecular docking and kinetic simulations revealed that Y50Bg4 has a higher affinity for cellobiose than for lactose and identified structural regions (residues 325–350 and 390–410) that contribute to its thermal stability.DiscussionThese findings highlight the potential of Y50Bg4 for industrial applications in bioethanol production and cellulose hydrolysis. In summary, Y50Bg4, with its exceptional enzymatic properties, presents significant application value and market potential in industrial sectors such as bioethanol production and cellulose hydrolysis.